Efficacy and Safety of Fruquintinib Plus PD-1 Inhibitors Versus Regorafenib Plus PD-1 Inhibitors in Refractory Microsatellite Stable Metastatic Colorectal Cancer - Sun, Liying; Huang, Shenglan; Li, Dan; Mao, Ye; Wang, Yurou; Wu, Jianbing (Frontiers in Oncology, 2021)
Background Microsatellite stability (MSS) or mismatch repair proficient (pMMR) metastatic colorectal cancer (mCRC) is resistant to immune checkpoint inhibitors. Studies have shown that antiangiogenic drugs combined with programmed death receptor-1 (PD-1) inhibitors can improve immunosuppression. The purpose of this study was to compare the efficacy of fruquintinib combined with PD-1 inhibitor (FP) and regorafenib combined with PD-1 inhibitor (RP) in the treatment of advanced mCRC with MSS or pMMR. Materials and Methods We retrospectively collected advanced MSS or pMMR mCRC patient data from The Second Affiliated Hospital of Nanchang, China, from June 2019 to March 2021. Then, we analyzed and compared the efficacy and safety of FP and RP. Results A total of 51 patients who met the criteria were divided into FP (n = 28) and RP groups (n = 23). The overall response rate of the FP and RP groups was 7.1% and 8.7% and the disease control rate was 89.3% and 56.5%, respectively. The median progression-free survival (PFS) time was higher in the FP group than in the RP group (6.4 vs. 3.9 months, respectively; P = 0.0209). Patients with no liver metastasis, KRAS wild type, and left colon tumor may benefit from FP. Eight patients (15.7%) had grade 3 toxicity related to treatment. Cox multivariate regression analysis showed that the treatment method was an independent risk factor for median PFS time. Conclusion Our study indicates that FP could improve PFS time of patients with advanced mCRC compared with RP.